Four-armed seated figure, likely of Shaiva affiliation - Temples of India Project Team (Jio Institute, 2024)
Idol obtained from Harsha Hill, now housed in the Government Museum, Sikar. The four-armed seated figure, likely of Shaiva affiliation, occupies a central place in the architectural fragment. He holds a trident and likely a staff in his upper two hands, while the lower hands hold a citron in the left hand and an unclear object in the right. While the figure lacks an ithyphallic representation, it could still be interpreted as Lakulisha. Flanking this central figure in the subset niches on either side are two apsaras.